Riverine forests in the upper Soča valley (the Julian Alps, western Slovenia) - Dakskobler, Igor; Šilc, Urban; Čušin, Boško (Hacquetia, 2015)
Riverine forests (willow stands and groves) along the upper course of the Soča River in western Slovenia were researched applying the standard Central-European phytosociological method (Braun-Blanquet 1964). After processing 52 relevés applying the hierachical classification and ordination method (PCoA) we determined two subassociations of the association Salicetum albae Issler 1926 (alliance Salicion albae Soó 1930): -myosotidetosum I. Kárpáti ex Soó 1958 and -leucojetosum verni Šilc, Čušin & Dakskobler 2004 subass. nova and two syntaxa from the alliance Alnion incanae Pawłowski in Pawłowski & Wallisch 1928: Lamio orvalae-Salicetum eleagni nom. prov. and Alnetum incanae Lüdi 1921 var. geogr. Anemone trifolia Müller & Görs 1958 forma Galanthus nivalis f. nova. As a specific successional stage (subassociation -caricetosum albae, differentiated by the species Tilia cordata, Carex alba and Carpinus betulus) we classified into the latter syntaxon also the stands which thrive on sites that are only rarely (occasionally) still flooded and where hydromorphic soil traverses into automorphic. Even regarding its floristic composition this community is transitional between the forests from the alliance Alnion incanae and the forests from the alliance Erythronio-Carpinion.